An Overview of the Atmospheric Component of the Energy Exascale Earth System Model. (5th August 2019) - Rasch, P. J.; Xie, S.; Ma, P.‐L.; Lin, W.; Wang, H.; Tang, Q.; Burrows, S. M.; Caldwell, P.; Zhang, K.; Easter, R. C.; Cameron‐Smith, P.; Singh, B.; et al.
Abstract: The Energy Exascale Earth System Model Atmosphere Model version 1, the atmospheric component of the Department of Energy's Energy Exascale Earth System Model is described. The model began as a fork of the well‐known Community Atmosphere Model, but it has evolved in new ways, and coding, performance, resolution, physical processes (primarily cloud and aerosols formulations), testing and development procedures now differ significantly. Vertical resolution was increased (from 30 to 72 layers), and the model top extended to 60 km ( 0.1 hPa). A simple ozone photochemistry predicts stratospheric ozone, and the model now supports increased and more realistic variability in the upper troposphere and stratosphere. An optional improved treatment of light‐absorbing particle deposition to snowpack and ice is available, and stronger connections with Earth system biogeochemistry can be used for some science problems. Satellite and ground‐based cloud and aerosol simulators were implemented to facilitate evaluation of clouds, aerosols, and aerosol‐cloud interactions. Higher horizontal and vertical resolution, increased complexity, and more predicted and transported variables have increased the model computational cost and changed the simulations considerably. These changes required development of alternate strategies for tuning and evaluation as it was not feasible to "brute force" tune the high‐resolution configurations, so short‐term hindcasts, perturbed parameter ensemble simulations, and regionally refined simulations provided guidance on tuning and parameterization sensitivity to higher resolution. A brief overview of the model and model climate is provided. Model fidelity has generally improved compared to its predecessors and the CMIP5 generation of climate models. Plain Language Summary: This study provides an overview of a new computer model of the Earth's atmosphere that is used as one component of the Department of Energy's latest Earth system model. The model can be used to help understand past, present, and future changes in Earth's behavior as the system responds to changes in atmospheric composition (like pollution and greenhouse gases), land, and water use and to explore how the atmosphere interacts with other components of the Earth system (ocean, land, biology, etc.). Physical, chemical, and biogeochemical processes treated within the atmospheric model are described, and pointers to previous and recent work are listed to provide additional information. The model is compared to present‐day observations and evaluated for some important tests that provide information about what could happen to clouds and the environment as changes occur. Strengths and weaknesses of the model are listed, as well as opportunities for future work. Key Points: A brief description and evaluation is provided for the atmospheric component of the Department of Energy's Energy Exascale Earth System Model Model fidelity has generally improved compared to predecessors and models participating in past international model evaluations Strengths and weaknesses of the model, as well as opportunities for future work, are described